Management Of Irrigation Water and its Impact on Agriculture Productivity - Asad Raza Abidi (Revista Română de Statistică, 2013)
On the inflow side canal water in the canal command area of Mirwah is mismanaged by irrigation officials and head-end and influential farmers. Farmers in Sindh generally and Khairpur particularly irrigate their land without scientific techniques and there is no economic pricing of water that might encourage conservation. This, together with the lack of any adequate substitute in the form of administrative control of water and cropping patterns, has been responsible for the excessive water-coefficient of output, and the unequal distribution of water, which have been at the heart of the problem of mismanagement water on the inflow side. The need for restructuring the irrigation system in Sindh is urgent not only because of both allocation and distribution, because, over the years, the province has suffered from unequal distribution of water between big and small farmers, and between head-end and tail-end farmers.